Effects of plasma expansion plumes in view of pulses laser irradiating centimeter-scale spherical space debris - Fang, Yingwu (Oficyna Wydawnicza Politechniki Wrocławskiej, 2023)
The objective of this article was to investigate the dynamic evolution behaviors of plasma expansion plumes by pulses laser irradiating centimeter-scale spherical space debris. A calculated model of centimeter-scale spherical space debris irradiated by pulses laser was firstly deduced based on FEM (finite element method)/COMSOL, and the action rules of plasma expansion plumes by pulses laser-generated irradiating the debris were simulated for different laser powers and action times. The results showed that the velocity of plasma expansion plumes was increased with the increase of laser powers and action times. Especially, when the laser power was 700 kW and the action time was close to 25 μs, the maximum velocity of plasma expansion plumes approached 1.91 km/s, and the diffusion radius of plasma expansion plumes was increased by about 2.5 mm. Further, the diffusion radius was about twice that of 400 kW when the action time reached about 48 μs. As a result, by simulating the transient flow process of nanosecond pulses laser irradiating small spherical space debris, the flow field evolution information and plasma plumes evolution characteristics of centimeter-scale space debris at nanosecond time resolution were revealed.
Optica Applicata, Vol. 53, 2023, nr 3, s. 363-375
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; plasma expansion plumes; pulse laser; centimeter-scale spherical space debris; dynamic model